The Role of the Self Organized Learning Environment (SOLE) Learning Model Assisted by E-learning Applications to Improve Motivation and Learning Outcomes - Ridwan Effendi; Soetarno Joyoatmojo; Cicilia Dyah Sulistyaningrum Indrawati (Budapest International Research and Critics University, 2022)
The purpose of this study was to increase students' motivation and learning outcomes through a self-organized learning environment (SOLE) learning model assisted by e-learning applications. This research uses the classroom action research method. The subjects of this study were students of class XI Marketing Department at SMK Negeri 1 Puhpelem in Wonogiri Regency, Indonesia. Data collection techniques using observation, interviews, questionnaires, tests, and analysis of documents and archives. The data collected were analyzed descriptively qualitatively and quantitatively. The results showed an increase in students' motivation and learning outcomes through the role of a self-organized learning environment (SOLE) learning model assisted by e-learning applications. The results of the study obtained a comparison of the increase in learning motivation and learning outcomes of students in class XI Marketing A SMK Negeri 1 Puhpelem at the pre-action stage by 34.86%, increasing in cycle 1 to 64.39% and increasing again in cycle 2 by 85.17%. Learning outcomes increased in the pre-action stage by 33.33%, increased in cycle 1 to 68.57%, and increased again in cycle 2 by 88.57%. learning motivation for class XI Marketing B SMK Negeri 1 Puhpelem at the pre-action stage was 33.12%, increased in cycle 1 to 67.35%, and increased again in cycle 2 by 86.25%. Learning outcomes increased in the pre-action stage by 31.25%, increased in cycle 1 to 74.29%, and increased again in cycle 2 by 91.42%.